Analisis Kebiasaan Konsumsi Nasi Mahasiswa Teknologi Pangan Universitas Pendidikan Indonesia di Tengah Dilema Impor Beras - Annisa Sakanti Tamir; Firman Aziz; Ryan Ferdiana; Areta Nararya Putri Setiadi; Zhafira Tsania Rasyiffah; Shavi Khalwa Khalisha; Fiina Lanahdiyan Najah; Rahmania Nur Saputra (MES Bogor, 2025)
This study examines rice consumption patterns among UPI Food Technology Students and the effectiveness of food diversification as a solution to rice dependence and increasing imports. The method used is descriptive with a qualitative approach through observation and interviews with a total of 5 respondents to understand consumption habits and openness to alternative carbohydrate sources. The results show that the majority of students still rely on rice as a staple food, while diversification efforts have not been effective due to taste preferences, limited access, and lack of socialization. However, there is potential for Food Technology students to develop local rice and try food alternatives in the future. The novelty of this research lies in the irony between student preferences and the availability of alternative carbohydrate sources. These findings can serve as a basis for more sustainable food education and development policies.